COVID-19 in Cancer Patients: A Case Study in Viet Nam - Vo, Tuyen Kim Cat; Huynh, Nhi Ngoc Yen; Nguyen, Dai Duc; Ta, Nguyen Ha; Nguyen, Minh Thien; Nguyen, Tai Van; Dang, Huy Thanh; Le, Ngoan Tran (Asian Pacific Journal of Environment and Cancer, 2020)
Objectives: The aim was to describe the characteristics and outcomes of treatments for coronavirus infection in cancer survivors in Viet Nam from 23 January to 6 May 2020. Methods: We accessed data registration and publication of cases tested positive with COVID-19 by the Ministry of Health in Viet Nam. Characteristics of reported positive cases included age, sex, sources of infection, nationality, the onset of symptoms, and history of chronic diseases. The outcomes included incubation, suspected, clinical course, and clearance time by the subgroup of patients having a history of cancer and non-cancer. T-test was used to compare two means of these groups. Results: Three men patients were cancer survivors (1.1% of 271 cases),a Chinese business aged 66 having lung cancer (ICD-10: C34), a Sweden tourism aged 64 having blood cancer (ICD-10: C81-C96), and a Vietnamese aged 71 having liver cancer (ICD-10: C22). The remaining 268 patients were free-cancer. The clinical course of three cancer survivors was 17.3 days that were shorter 3.2 days when compared to non-cancer, p=0.2068. The estimated suspected time was longer in cancer survivors (5.3 days) than non-cancer (1.5 days), p =0.0394. The mean age was older in cancer survivors (67-year-old) than non-cancer (35.5-year-old), p =0.0003. Conclusions: Cancer survivors might be at high risk of COVID-19 infection due to their underlying vulnerable health condition related to cancer disease and they need extra care to minimize the risk of infection from coronavirus.